Strategies to enhance sexual health education for prevention of teenage pregnancy in Vhembe District, Limpopo Province: different stakeholder's perspectives, a co-operative Inquiry qualitative protocol paper - Nombulelo V. Sepeng; Fhumulani M. Mulaudzi; Pfarelo Mathivha; Maurine R. Musie; Raikane J. Seretlo (BMC, 2023)
Abstract Background South Africa is reporting higher rates of adolescent pregnancy as compared to other countries. There are different types of interventions that are in place to address teenage pregnancy. However, these interventions were developed using top-down strategy without the inclusion of different stakeholders and adolescents which makes it hard to implement those interventions particularly in countries like South Africa. Hence, this study aimed to develop strategies to enhance sexual health education for prevention of teenage pregnancy in Vhembe District, Limpopo Province of South Africa. Methods The research design of this study will be Co-operative Inquiry.The study will take place in Vhembe District in Limpopo province of South Africa through collaborating with a Non-governmental Organisation (NGO). The study population will be the teenagers and all the different stakeholders caring for teenagers in their areas of specialization. Purposive sampling will be used to sample the targeted participants of the study. The data collection method will be done in phases and focus group discussions will be used to collect data. Content analysis will be used to analyse data. Discussion This study will add to the body of knowledge regarding the strategies that maybe used to enhance sexual health education for prevention of teenage pregnancy.